OPTIMALISASI PERAN CORPORATE SOCIAL RESPONSIBILITY DALAM INTERVENSI PENANGANAN STUNTING DI KABUPATEN BATANG - Setiawan, Hendy; Febriani Daud, Rosy (Bapelitbang Kabupaten Batang, 2025)
This paper aims to discuss optimizing the role of corporate social responsibility (CSR) in stunting interventions in Batang Regency. The government's limited budget for stunting has opened up options for CSR interventions as a solution. CSR programs embedded in the industrial sector have played a crucial role. Besides serving as public communication for companies about their existence, they also serve as a form of strategic partnership with the government. Similarly, the Batang Regency Government has partnered with the private sector in stunting management. Optimizing the role of CSR is crucial to achieving zero stunting as expected. This research method uses a qualitative approach with a literature review approach. Data were collected from secondary data sources and then processed using the Miles and Hubberman qualitative data analysis model. The research findings indicate the need to optimize private sector involvement through more comprehensive CSR initiatives in stunting interventions in Batang Regency. This optimization is crucial to achieve significant and sustainable reductions in stunting. Therefore, the local government needs to engage with all sectors of the private sector through CSR initiatives to significantly impact the reduction of remaining stunting.